2010
DOI: 10.1523/jneurosci.2948-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Inputs Contribute to Phasic Activity in Vasopressin Neurons

Abstract: Many neurons in the CNS display rhythmic patterns of activity to optimize excitation-secretion coupling. However, the mechanisms of rhythmogenesis are only partially understood. Magnocellular vasopressin (VP) neurons in the hypothalamus display a phasic activity that consists of alternative bursts of action potentials and silent periods. Previous observations from acute slices of adult hypothalamus suggested that VP cell rhythmicity depends on intrinsic membrane properties. However, such activity in vivo is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…This sustained activity, either in bursts of APs for OT neurons or phasic for VP neurons, is known in vivo to specifically allow the release of boluses of neurohormone into the blood stream 14 . The electrical activities of OT and VP neurons are quite similar in organotypic cultures and in vivo 17,28 , and the ability of OT neurons to burst in vitro fully recapitulates the known programme of sexual differentiation of the hypothalamus 15 . Thus, we likely provide here evidence for the existence of two separate neuroendocrine pattern (or pulse) generators 7 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This sustained activity, either in bursts of APs for OT neurons or phasic for VP neurons, is known in vivo to specifically allow the release of boluses of neurohormone into the blood stream 14 . The electrical activities of OT and VP neurons are quite similar in organotypic cultures and in vivo 17,28 , and the ability of OT neurons to burst in vitro fully recapitulates the known programme of sexual differentiation of the hypothalamus 15 . Thus, we likely provide here evidence for the existence of two separate neuroendocrine pattern (or pulse) generators 7 .…”
Section: Discussionmentioning
confidence: 77%
“…Neurons that did not display spontaneous bursting activity after 15-20 min of recording were subjected to three phenotyping challenges. Either exogenous OT or bicuculline was applied to trigger bursts or oscillatory activity, respectively; if these approaches were inefficient, a hyperosmotic test ( þ 25 mOsm) was administered to reveal phasic activity typical of vasopressinergic neurons 17 . On rare occasions these tests were negative, and triple-labelling immunocytochemistry was performed to reveal biocytin, OT and VP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process could thus serve to reduce the impact of excitatory inputs on VP neuron firing, enabling these cells to develop a more autonomous activity. This could be important for the rhythmic phasic activity displayed by VP neurons in response to physiological stimulation, such as dehydration or hemorrhage, which is believed to depend on both intrinsic membrane properties and extrinsic synaptic influence (Israel et al, 2010).…”
mentioning
confidence: 99%
“…In the present study, TNFR1 immunoreactivity was identified in dendritic profiles receiving excitatory-type synapses characteristic of glutamate inputs (Peters et al, 1991). Glutamate activity in the PVN plays a critical role in homeostasis by influencing behavioral (Hettes et al, 2003), metabolic (Amir, 1990, Kalsbeek et al, 2008), neuroendocrine (Hattori et al, 1992, Feldman and Weidenfeld, 1997, Israel et al, 2010), and autonomic (Yeh et al, 1997, Zhang and Fogel, 2002, Crestani et al, 2010) processes. In particular, glutamate signaling in the PVN is an established central coordinator of sympathetic outflow critically involved in cardiovascular regulation (Ferguson et al, 2008, Kc and Dick, 2010).…”
Section: Discussionmentioning
confidence: 99%